2006
DOI: 10.2165/00063030-200620040-00003
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping Beauty Transposon-Mediated Nonviral Gene Therapy

Abstract: Safe and effective delivery of genetic material to mammalian tissues would significantly expand the therapeutic possibilities for a large number of medical conditions. Unfortunately, the promise of gene therapy has been hampered by technical challenges, the induction of immune responses, and inadequate expression over time. Despite these setbacks, progress continues to be made and the anticipated benefits may come to fruition for certain disorders. In terms of delivery, nonviral vector systems are particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 115 publications
1
15
0
Order By: Relevance
“…This is the first study to our knowledge in which LSECs were targeted to express FVIII transgene in a knockout mouse model of hemophilia A, confirming the results of an LSEC transplantation study that also reported correction of FVIII deficiency in this mouse model (53). However, 2 previous SB-Tn gene therapy studies have described the replacement of FVIII in liver via hydrodynamic delivery (54); and lung endothelial cells using linear polyethylenimine (40). Nevertheless, in targeting only the LSECs, we were able to treat adult immunocompetent hemophilia A mice effectively without apparent induction of inhibitor formation.…”
Section: Figuresupporting
confidence: 77%
See 2 more Smart Citations
“…This is the first study to our knowledge in which LSECs were targeted to express FVIII transgene in a knockout mouse model of hemophilia A, confirming the results of an LSEC transplantation study that also reported correction of FVIII deficiency in this mouse model (53). However, 2 previous SB-Tn gene therapy studies have described the replacement of FVIII in liver via hydrodynamic delivery (54); and lung endothelial cells using linear polyethylenimine (40). Nevertheless, in targeting only the LSECs, we were able to treat adult immunocompetent hemophilia A mice effectively without apparent induction of inhibitor formation.…”
Section: Figuresupporting
confidence: 77%
“…In addition, unmethylated cytosine-guanine dinucleotide (CpG) (38), transgene structure, and protein product may also contribute to poor transduction efficiency and reduced persistence of gene expression (39). Although proof-of-principle studies using hydrodynamic delivery have established the potential of SB-mediated insertion into the liver genome for long-term gene correction (40), the delivery is nonselective. Thus, an efficient cell type-specific tar-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SB was the first transposon ever shown capable of efficient transposition in vertebrate cells, thereby enabling new avenues for genetic engineering in animal model species (reviewed in Ivics et al, 2009) as well as for human gene therapy (Yant et al, 2000;Ivics and Izsvak, 2006). As a nonviral alternative to viral vectors, the potential of the SB system has been thoroughly probed (Izsvák and Ivics, 2004;Fernando and Fletcher, 2006;Ivics and Izsvak, 2006;VandenDriessche et al, 2009;Hackett et al, 2010;Izsvák et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, synthetically produced mRNA can serve as a source of the transposase, thereby limiting the duration of transposase expression and lowering the risk of ''rehopping'' of the already integrated transposon-based vector (Wilber et al, 2006). Chromosomal integration of SB transposons is random, which is potentially mutagenic (see below), but no SB-associated adverse effects have been observed in preclinical animal studies (Fernando and Fletcher, 2006;Ivics and Izsvak, 2006;Hackett et al, 2010;Izsvák et al, 2010). Last, SB transposons can be harnessed to integrate plasmid-based small hairpin RNA (shRNA) expression cassettes into chromosomes to obtain stable knockdown cell lines by RNA interference (Fig.…”
Section: Introductionmentioning
confidence: 99%